2021
DOI: 10.1021/acs.biomac.1c00513
|View full text |Cite
|
Sign up to set email alerts
|

Control Release of Adenosine Potentiate Osteogenic Differentiation within a Bone Integrative EGCG-g-NOCC/Collagen Composite Scaffold toward Guided Bone Regeneration in a Critical-Sized Calvarial Defect

Abstract: The regeneration of critical-sized bone defects with biomimetic scaffolds remains clinically challenging due to avascular necrosis, chronic inflammation, and altered osteogenic activity. Two confounding mechanisms, efficacy manipulation, and temporal regulation dictate the scaffold’s bone regenerative ability. Equally critical is the priming of the mesenchymal stromal cells (MSCs) toward lineage-specific differentiation into bone-forming osteoblast, which particularly depends on varied mechanochemical and biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Accordingly, other findings obtained by Verma et al [138] showed that an osteogenic scaffold comprising adenosine/epigallocatechin gallate-N,O-carboxymethyl chitosan/collagen type I (AD/EGCG-g-NOCC@clgn I), exhibited osteo-inductive properties in a calvarial defect model reproduced in BALB/c mice. The ex-vivo findings clearly established the proosteogenic potential of adenosine and EGCG, which both stimulated MSCs toward osteoblast differentiation as evaluated by the increased expression of selective osteogenic markers such as alkaline phosphatase and osteocalcin and enhanced calcium deposits.…”
Section: Clinical Perspectivesmentioning
confidence: 82%
“…Accordingly, other findings obtained by Verma et al [138] showed that an osteogenic scaffold comprising adenosine/epigallocatechin gallate-N,O-carboxymethyl chitosan/collagen type I (AD/EGCG-g-NOCC@clgn I), exhibited osteo-inductive properties in a calvarial defect model reproduced in BALB/c mice. The ex-vivo findings clearly established the proosteogenic potential of adenosine and EGCG, which both stimulated MSCs toward osteoblast differentiation as evaluated by the increased expression of selective osteogenic markers such as alkaline phosphatase and osteocalcin and enhanced calcium deposits.…”
Section: Clinical Perspectivesmentioning
confidence: 82%
“…Bone healing is an intricate process involving a series of molecular and cellular events that are evolutionarily conserved [148]. In the realm of critical size bone injuries, two strategies are currently gaining prominence in clinical applications.…”
Section: Cellular Events During Bone Regeneration With Scaffoldsmentioning
confidence: 99%
“…One approach focuses on utilizing scaffolds with bioresponsive elements, including osteoconductive and osteoinductive components, to stimulate the inherent cellular environment consisting of immune cells and stem/stromal progenitor cells. This stimulation aids in enhancing the healing and regeneration of bone [148]. The other approach revolves around in situ ectopic cellular reprogramming, achieved through the delivery of transcription and trophic factors, RNA-based therapies, manipulation of epigenetic factors using suitable biomaterials, and even in vivo gene editing [149].…”
Section: Cellular Events During Bone Regeneration With Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a growing body of attention has been focused on adenosine and adenosine receptors as factors implicating in bone regeneration [ 28 ]. Exogenous adenosine supplementation is an effective method in order for successful osteogenic differentiation of mouse BMMSCs [ 71 ]. Also, administration of exogenous adenosine as a differentiation factor to cultured human ESCs has enhanced osteogenesis through A2b receptor adenosine signaling.…”
Section: Small Moleculesmentioning
confidence: 99%